Consultants pris entre « l’arbre et l’écorce » ou comment concilier « vendre du conseil » et co-construire l’intervention ? - Marie-Josée Lorrain; Cécile Nicolas (Communiquer)
How do consultants address the social issue of co-production of the intervention? How do they envision cooperation in co-production activities? It is from these questions that the effects of neo-productivist organizational transformations on communicational practices of organizational development consultants are addressed. Little research links the issues related to communicational practices and the organizational transformations in which they are carried out, with an emphasis on the recognition of consultants. Based on qualitative materials, we observe the question of the subjective commitment of consultants in their communication activity and we highlight certain tensions. The analysis shows that in order to encourage the mobilization of cooperation as the aim of intersubjectivity in the consulting-intervention, it seems necessary to solicit a theoretical multidisciplinary approach in order to take the measure of all the fields concerned (management, clinical approaches to work, …) by these issues as well as to open up new training opportunities.